Experimental and numerical study of impeller modification to improve the performance of centrifugal pump for handling viscous liquids - Heru Mirmanto; Triyanto Jiwandono; Dedy Zulhidayat Noor; Dika Andini Suryandari; Joko Sarsetiyanto (Faculty of Vocational Studies - Research Center, DRPM ITS, 2025)
The impeller is a crucial component of a centrifugal pump, as it converts shaft power into fluid energy. There are three main types of impellers: closed, semi-open, and open, each with distinct characteristics when handling different working fluids. Fluid viscosity can significantly affect pump performance. Closed impellers are particularly effective for pumping water; however, their performance decreases when handling high-viscosity fluids. Modifications to closed impellers can be implemented to address this decline in performance. In contrast, semi-open impellers are better suited for managing highviscosity fluids than closed impellers. Both experimental and numerical methods were used in this study. Measurements of performance were acquired through the construction of a pump testing facility. Modifications and variations in the shape of the impeller were created using 3D printing techniques with polylactic acid (PLA) as the material. In addition, the experimental results are strengthened by pressure contour analysis in numerical simulations. When pumping molasses at 65 lpm, the highest performance was achieved with a closed impeller, which attained a head of 7,9 m, an efficiency of 17.8%. Conversely, a 6-blade semi-open impeller, achieving a head of 12,2 m, an efficiency of 29%. So, this modification can improve the Head by 54,4 % and the efficiency by 63%.